Molecular Epidemiology of Candida auris in Colombia Reveals a Highly Related, Countrywide Colonization With Regional Patterns in Amphotericin B Resistance (2019)
ABSTRACT: Background: Candida auris is a multidrug-resistant yeast associated with hospital outbreaks worldwide. During 2015-2016, multiple outbreaks were reported in Colombia. We aimed to understand the extent of contamination in healthcare settings and to characterize the molecular epidemiology of C. auris in Colombia. Methods: We sampled patients, patient contacts, healthcare workers, and the environment in 4 hospitals with recent C. auris outbreaks. Using standardized protocols, people were swabbed at different body sites. Patient and procedure rooms were sectioned into 4 zones and surfaces were swabbed. We performed whole-genome sequencing (WGS) and antifungal susceptibility testing (AFST) on all isolates. Results: Seven of the 17 (41%) people swabbed were found to be colonized. Candida auris was isolated from 37 of 322 (11%) environmental samples. These were collected from a variety of items in all 4 zones. WGS and AFST revealed that although isolates were similar throughout the country, isolates from the northern region were genetically distinct and more resistant to amphotericin B (AmB) than the isolates from central Colombia. Four novel nonsynonymous mutations were found to be significantly associated with AmB resistance. Conclusions: Our results show that extensive C. auris contamination can occur and highlight the importance of adherence to appropriate infection control practices and disinfection strategies. Observed genetic diversity supports healthcare transmission and a recent expansion of C. auris within Colombia with divergent AmB susceptibility.